Effect of sulfuric acid pretreatment on biogas production from Salvinia molesta. Issue 1 (February 2019) - Syaichurrozi, Iqbal; Villta, Putri Kurnia; Nabilah, Nabilah; Rusdi, Rusdi
Highlights: Pretreatment decreased and increased the fiber and non-fiber carbohydrate respectively. Pretreatment produced higher total biogas yield than unpretreatment case. Pretreatment using concentration of 2–4% decreased the lag time in biogas production. Pretreatment using concentration 6% caused the long lag time in biogas production. Modified Gompertz was more suitable than first order kinetic model. Abstract: The effect of sulfuric acid pretreatment on biogas yield from Salvinia molesta (SM) was studied. The sulfuric acid concentration was varied to be 2, 4, 6% v/v. Pretreatment was carried out under batch system at room temperature and pressure of 1 atm for two days. Then, the digestion was carried out for 30 days under batch system at room temperature and pressure of 1 atm. The pretreatment decreased the lignin content and increased the nitrogen free extract content (non-fiber carbohydrate). The more the sulfuric acid concentration, the more the change of these contents. Furthermore, cumulative biogas yield from pretreated SM using sulfuric acid 2–6% (22.72–24.14 mL/g VS) was higher than that from raw SM (13.28 mL/g VS). For digestion during 30 days, the best pretreatment was 4% because it produced the highest total biogas yield (24.14 mL/g VS) and had very short lag time (0 day). The measured data was simulated using the modified Gompertz and first order kinetic model. The calculation showed that the modified Gompertz model (error 6.141–12.431%) was better than the first order kinetic model (error 7.336–47.606%).